A pilot study of serum anti-müllerian hormone in polycystic ovary syndrome and its relationship with insulin resistance, lipid profile and adiponectin - Jun, Thien Jun (2018)
Objectives: This study was done to estimate the level of serum anti-Müllerian hormone (AMH) in patients with polycystic ovary syndrome (PCOS) and to correlate serum AMH level with insulin resistance, lipid profile and adiponectin levels. Study design: This cross sectional study was conducted at Hospital Universiti Sains Malaysia (HUSM), Health Campus, Kubang Kerian, Kelantan, Malaysia. Total of thirty (30) women (aged 18-40 years old) diagnosed with PCOS were recruited from patients attending gynaecology clinic between July 2016 and April 2017. Fasting venous blood sample were collected from all subjects. Serum AMH, insulin, adiponectin, triglycerides, high-density lipoprotein cholesterol (HDL-C), and plasma glucose levels were measured. Insulin resistance was calculated based on homeostasis model of assessment-insulin resistance (HOMA-IR). The serum AMH level was estimated by using descriptive analysis and the correlation of serum AMH level with the metabolic parameters were analysed by using either Pearson correlation or Spearman correlation. Results: The median of serum AMH levels in women with PCOS was 6.8 ng/mL (IQR: 7.38 ng/mL). There was a significant negative correlation between serum AMH and HOMA-IR or triglycerides levels (r = -0.49, p = 0.006 and r = -0.55, p = 0.002, respectively). A significant positive correlation was observed between serum AMH and serum HDL-C or serum adiponectin levels (r = 0.56, p = 0.001 and r = 0.44, p = 0.014, respectively) in all study subjects. Conclusion: The serum AMH level in patients with PCOS is associated with HOMA-IR, triglycerides, HDL-C and adiponectin levels. Therefore, this pilot study suggested that AMH may be used as a potential cardiometabolic risk marker in women with PCOS.